Anteseden Pertumbuhan Ekonomi: Pendapatan atau Belanja Daerah? - Mesri Welhelmina Nisriani Manafe; Herny Constantin Fanggidae; Alya Elita Sjioen; Boy Supriyana Effendi (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
Productive spending is an indication for capital spending efficiency in line with increasing in PAD and economic growth. Therefore, it is important to know the movement pattern of revenues and expenditures to accelerate welfare transfer’s to the community. This study aims to measure the role of capital expenditure and non-transfer income to encourage the rate of economic growth as a control form over local government fiscal policy. 88 data  for 2015-2018 period in 22 districts/cities in NTT. Results show support for H0 for the relationship between capital spending and economic growth and PAD that is not in line with the spend-revenue hypothesis. While PAD shows an effect on the rate of economic growth but does not become the interaction variable required in the relationship. The results of the study contribute to government in strengthening regional spending capacity as a form of spending efficiency and exploring regional revenues to reduce fiscal dependence and for central government as transfer funds evaluation to achieve national development goals. Theoretically, the results studied support previous research on the relationship between PAD and economic growth but not on the relationship between capital expenditures and economic growth and the ability of PAD as an interaction variable. Limitation in this study is the determination relationship direction between variables without sample considered and there is only an interaction variable.